(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Salinity is a serious threat to the crop production in the southern region of Bangladesh and it is especially important during dry period of a year. A study was undertaken to examine the changes in water and soil salinity over the period from February to April, 2014 at Kalapara upazila of Patuakhali district. Water samples were periodically collected from lake, pond, earthen well, deep tube-wells (5, 15 and 30 km away from the sea) and rivers (Tulatoli, Khaprabhanga, Sonatala and Andharmanik). Soil sampling was done from different crop fields (mustard, sweet gourd, potato, chilli, Khira-cucumber) and water melon and also from Sonatala and Andharmanik River flooded soils inside and outside polders. The electrical conductivity (EC) value of lake and pond waters was below 4 dS/m showing quite safe for irrigation while the EC value of earthen well exceeded 4 dS/m which are suitable in April. Water salinity of deep tube-wells (DTWs) increased as the DTW was closer to the sea, however all EC values were below 4 dS/m that suitable for irrigation, but not suitable for drinking purpose. Salinity level of all rivers tended to rise with the advancement of drying period, and for all dates of sampling, the EC value showed more than 4 dS/m. Soil salinity varied between inside and outside polder, and between mustard and sweet gourd fields, the higher EC values were observed outside polder and in the sweet gourd field. Soil EC levels were all above 4 dS/m particularly in April, crops showed varying degrees of leaf injury depending on the types of crops and extent of soil salinity. The EC values were positively correlated with Na and K contents of soil. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22218 J. Environ. Sci. & Natural Resources, 7(2): 111-114 2014